On our own, together : peer programs for people with mental illness (Book collections on Project MUSE., 2005)
"On Our Own, Together looks in depth at eight successful peer-run programs for adults with serious mental illness. The book grew out of a 1998 meeting that led off a nationwide study to assess not only the effectiveness of consumer-operated services programs but also their implications for the future of mental health care in the United States."--Jacket